Unfolding Meanings: Some Considerations for Qualitative Interview Studies - İsmail Özgür Soğancı (Anı Publishing, 2013)
t. Inside interpretivist paradigm, the repertoire of approaches have been enlargened in the last two decades with the popularity of qualitative research practice. While this present new opportunities to craft better social science texts, it also confuses scientists especially when they are in the process of forming research designs in their early field work experience. Based on my past research experience, during and after my doctoral studies, this paper suggests a set of ideas that might clarify some basic considerations regarding descriptive studies which attempt to unfold people's understandings through interview conversations. For this purpose, the study discusses some selected considerations regarding episthemological stance, method and textual possibilities. Informed mainly by hermeneutics, the set of ideas presented here aims at providing the readers with the qualities that leads to genuine mode of understanding, sharing with them information on how traditional concepts of "validity" and "analysis" can apply to qualitative studies, and making suggestions on the possibility of crafting richer texts for qualitative interview studies.